Come stordire e abbattere i conigli. Istruzioni tecniche, considerazioni filosofiche - Adinolfi, Massimo (Mechane, 2025)
The paper presents two panels. The first one looks at what happens or, rather, what should happen according to the regulations adopted by the European Union during procedures for the killing of farm animals: a technique is recommended, which should spare the animal unnecessary suffering. Technique and cruelty, technique and humanity, technique and sensitivity, technique and politics: there are many knots that are knotted here. The second panel builds on another animal, duck or rabbit, drawn by J. Jastrow, to raise questions not of the psychology of perception but, in a broader sense, of the politics of images, digital profiling, and social control. Both one picture and the other, in different forms and ways, try to consider the lateral deviations, opening effects, and shifts in meaning that technique can induce. The hypothesis to be suggested is that certainly technique establishes a certain regime of visibility, in its own and specific ways: it forces one to see things in a certain way. But it is also, at the same time, a force of indeterminacy, of breaking niches or environmental circles, and thus not necessarily a place of capture but also, at least potentially, a point of escape.